The System of Higher Education in Ukraine During the Years of Independence: a Cartographic Study - Bondarenko, E. L.; Dudun, T. V. (Ukrainian Geographical Journal, 2025)
The article is dedicated to the study of the higher education system in Ukraine throughout its modern history: from the time of gaining independence in 1991 to the present. For this purpose, the authors have chosen the cartographic method as one of the sufficiently rational and productive means, which allows for the most visual representation of the functioning of various aspects of the higher education system at certain stages of development. Maps allow for the simultaneous depiction of the structure of higher education, the composition of its main components, existing interconnections, trends, and also to forecast the prospects of the higher education system in space. The goal of the study is achieved by combining the cartographic method with a set of general scientific and specialized methods, forming its methodology. Analysis and synthesis, deduction, classification, information method, geoinformation mapping, and a systematic approach made it possible to effectively organize the work on studying the higher education system in Ukraine. The authors substantiated a list of main principles that outlined the content of the created maps, the framework of their application, and determined the reliability and relevance of the studies of the higher education system. These principles are scientific expediency, completeness and reliability, unconventionality, and evaluativeness. The classification feature of the created maps by types was chosen based on their functionality. It was determined that the primary maps are inventory maps, which present the state of the territory and mapping indicators for a specific period of time. It is noted that based on inventory maps, it is advisable to create evaluation maps, the content of which consists of mapping indicators formed through calculations and providing an assessment of a phenomenon or process from a certain perspective or in relation to another phenomenon (process). The targeted acquisition of necessary integrated working information about the research object allows for the creation of recommendation maps. These maps reflect the results of data analysis by presenting integrated information based on various approaches and methods in the evaluation of phenomena and processes in the higher education system. The final stage of using the cartographic method in studying the higher education system is the creation of forecast maps, which indicate the state of the research territory considering the implemented measures. The result of the study was a series of six maps. One map is an inventory map, three are evaluation maps, one is a recommendation map, and one is a forecast map.